1972
DOI: 10.1063/1.1693961
|View full text |Cite
|
Sign up to set email alerts
|

Theory and Simulation of the Beam Cyclotron Instability

Abstract: A detailed theory in conjunction with the results of computer simulation experiments is presented for the beam cyclotron instability. The main results are (1) After a period of exponential quasilinear development, turbulent wave-particle interactions cause cross-field diffusion of the electrons which smears out the electron gyroresonances. This occurs at a level of turbulence which scales as Σκ(| Eκ |2/4πN0Te)∼(Ωe/ωe)2(Ωe/kve), where Ωe and ωe are the electron cyclotron and plasma frequencies, and results in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
1

Year Published

1979
1979
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(63 citation statements)
references
References 12 publications
6
56
1
Order By: Relevance
“…In spite of the consensus that saturation of the beam-cyclotron instability via resonance broadening occurs at a low level of electric field turbulence (Lampe et al, 1972;Biskamp, 1973 and Lemons and Gary, 19781, it is riot clear that this will be true for solar wind parameters. The cr cal amplitude of the turbulent fields when resonance broadening becomes important was found by Lampe et al [1972] to be E = 960(NTe(ae/we)'(1/kaa))112 (mV/m), with T measured in eV.…”
Section: Forward and Reverse Shocksmentioning
confidence: 97%
See 2 more Smart Citations
“…In spite of the consensus that saturation of the beam-cyclotron instability via resonance broadening occurs at a low level of electric field turbulence (Lampe et al, 1972;Biskamp, 1973 and Lemons and Gary, 19781, it is riot clear that this will be true for solar wind parameters. The cr cal amplitude of the turbulent fields when resonance broadening becomes important was found by Lampe et al [1972] to be E = 960(NTe(ae/we)'(1/kaa))112 (mV/m), with T measured in eV.…”
Section: Forward and Reverse Shocksmentioning
confidence: 97%
“…As in Figure 8, V SW=450 km s -1 , N=7 cm -3 , B=5 y, and -e /T i -3. The results are shown in a relationship derived by Lampe et al [1972] for the case T »T i . Although the ratio ym /w is rather small, ranging from 5x10 -3 -5x10 -2 , ym is 5-6 times greater than found for the MTSI (cf.…”
Section: Forward and Reverse Shocksmentioning
confidence: 99%
See 1 more Smart Citation
“…ECDI-driven waves are important for shock physics because they are capable of resonantly interacting with the bulk of the ion distribution and preferentially heating the electrons perpendicular to B o [Forslund et al, 1970[Forslund et al, , 1972Lampe et al, 1972]. More recent work has shown that the ECDI can produce a suprathermal tail on the ion distribution and can strongly heat the electrons [Muschietti and Lembège, 2013].…”
Section: A1 Themis Examplesmentioning
confidence: 99%
“…The typical growth rates for the observed modes are k : ≤ lh (or ≤20-200 rad/s) [e.g., Lampe et al, 1972;Forslund et al, 1972;Muschietti and Lembège, 2013] for the ECDI, ∼ 10 −2 pi (or ∼30-90 rad/s) [e.g., Dum et al, 1980;Akimoto and Winske, 1985;Petkaki et al, 2006] for IAWs, ≤ 10 −1 Ω ce (or ∼88-880 rad/s) [e.g., Dum et al, 1980;Moreira, 1983;Baumjohann et al, 1999] for the high-frequency whistler mode waves, and ≤ 10 −1 pe [e.g., Omura et al, 1996] for ESWs. Therefore, when the wave amplitudes are large B ≫ k for the ESWs and ⋙ k for the ECDI, IAWs, and high-frequency whistler mode waves.…”
Section: Appendix A: High Frequency Wavesmentioning
confidence: 99%